2010
DOI: 10.3168/jds.2009-2839
|View full text |Cite
|
Sign up to set email alerts
|

Linear relationship between increasing amounts of extruded linseed in dairy cow diet and milk fatty acid composition and butter properties

Abstract: The aim of this experiment was to compare the effects of increasing amounts of extruded linseed in dairy cow diet on milk fat yield, milk fatty acid (FA) composition, milk fat globule size, and butter properties. Thirty-six Prim'Holstein cows at 104 d in milk were sorted into 3 groups by milk production and milk fat globule size. Three diets were assigned: a total mixed ration (control) consisting of corn silage (70%) and concentrate (30%), or a supplemented ration based on the control ration but where part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
78
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 29 publications
22
78
3
3
Order By: Relevance
“…This result is in agreement with Timmen and Patton (1988), Fauquant et al (2005), Rahmatyar and Wiking (2012) and Mesilati-Stahy and Argov-Argaman (2014) who have shown that the small MFG, in comparison with the large MFG from the same milk, have higher contents in PUFA, MUFA and lower contents in short SFA (de novo synthesized). This result could be partly linked to the feeding treatments reported in SMFG group (grazing, lipid supplementation mainly) as shown by Couvreur et al (2006) and Lopez et al (2014) with a pasture-based diet or by Hurtaud et al (2010) with a maize silage-based diet supplemented with extruded linseed. Moreover, FA profile differences between LMFG, MFGM milk and MFGM yield milk are weak.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This result is in agreement with Timmen and Patton (1988), Fauquant et al (2005), Rahmatyar and Wiking (2012) and Mesilati-Stahy and Argov-Argaman (2014) who have shown that the small MFG, in comparison with the large MFG from the same milk, have higher contents in PUFA, MUFA and lower contents in short SFA (de novo synthesized). This result could be partly linked to the feeding treatments reported in SMFG group (grazing, lipid supplementation mainly) as shown by Couvreur et al (2006) and Lopez et al (2014) with a pasture-based diet or by Hurtaud et al (2010) with a maize silage-based diet supplemented with extruded linseed. Moreover, FA profile differences between LMFG, MFGM milk and MFGM yield milk are weak.…”
Section: Discussionmentioning
confidence: 93%
“…The relevant factors reported in the literature are the diet composition (forage composition, lipid supplementation), the breed or the individual variability. For instance, the average MFG diameter is 0.3 µm lower in Holstein cows (3.3 µm) in comparison with Normandy cows (3.6 µm) Logan et al, 2014); in comparison with a maize silage-based diet, it decreases down to 0.3 to 0.4 µm when cows are fed on pasture (3.4 v. 3.1 µm, respectively) or on a supplemented maize silage diet with linseed oil (4.2 v. 3.8 µm, respectively) (Couvreur et al, 2006 andHurtaud et al, 2010;Lopez et al, 2014) and down to −0.2 µm with high-concentrate low-forage diets . It is modulated by the lactation stage (Mesilati-Stahy and Argov-Argaman, 2014; Altenhofer et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…The extent of change in milk FA concentration is generally proportional to the level of inclusion of linseeds in the diet (Ferlay et al, 2013;Glasser et al, 2008a). The effects of increasing amounts of extruded linseeds in the diet have been studied by different authors (Brunschwig et al, 2010;Ferlay et al, 2013;Hurtaud et al, 2010). The major changes concern increases in trans-18:1 and total conjugated linoleic acid (CLA) concentrations in milk.…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 99%
“…1. Effect of increasing amounts of 18:3 n-3 intake from linseeds on milk 18:3 n-3 proportion (from Chilliard et al, 2009;Ferlay et al, 2013;Hurtaud et al, 2010). Equation of linear regression is: Y = 0.0018X + 0.38 (R 2 = 0.59), where Y is milk 18:3 n-3 proportion (g/100 g of total FA) and X is 18:3 n-3 intake (g/d).…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 99%
“…Milk higher in monounsaturated FA composition impacted the physical properties of the butter, cheese, yogurt, and ice cream (Chen et al 2004). Extruded linseed altered the FA composition of milk, which impacted butter firmness, fat loss in buttermilk, and butter moisture (Hurtaud et al 2010). FA composition of the diet impacted the size of the milk fat globules (Briard et al 2003;Wiking et al 2004;Carroll et al 2006) with large milk fat globules more susceptible to coalescence.…”
Section: Introductionmentioning
confidence: 99%